Hadith Text Classification on Sanad Part Using Edge List - Nursyahidah, Alias; Nurazzah, Abdul Rahman; Normaly Kamal, Ismail; Zulhimi, Mohamed Nor; Muhammad Nazir, Alias; Mohd Sham, Kamis (2023)
Hadith has two components consisting of sanad and the content parts. Most of the studies in hadith text classification focus on the content part named topical classification area. The sanad part, on the contrary, gains less attention in the text classification area. In this study, we design classification rules to classify hadith text based on the sanad part using the edge list concept. The rule-based classification is designed by using 700 hadith texts as a training data set and 300 hadith texts for the testing data set. We evaluate the results by using precision and recall measurement. The precision value is 1.00 by developing the rule-based classification on knowledge from experts. In our study, the recall value was 0.11 because the chronological lists for hadith text in the training set did not represent all chronological lists in Shahih Bukhari hadith, which is more than 7000. In the future, this study can be extended to analyse the overall text classification from Shahih Bukhari.